Binder-free silicon / carbon nanotube composite carbon fiber negative electrode material, preparation method thereof and application in lithium ion structure energy storage composite material

By growing carbon nanotubes on carbon fibers and depositing nanosilicon on their surfaces to form a binder-free silicon/carbon nanotube composite anode material, the problems of low specific capacity and volume expansion of the existing lithium-ion battery anode material are solved, and high energy density and excellent cycling stability are achieved.

CN119852398AInactive Publication Date: 2025-04-18BEIJING INST OF TECH

Patent Information

Application Number
CN202510027105.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The negative electrode material of existing lithium-ion batteries is difficult to meet the needs of the new energy field because of its low specific capacity. Although silicon materials have a higher theoretical specific capacity, they fail due to volume expansion during the battery cycle.

Method used

Using a binder-free silicon/carbon nanotube composite carbon fiber anode material, a stable silicon/carbon nanotube bonding structure is formed by uniformly growing carbon nanotubes on the carbon fibers and depositing nanosilicon by magnetron sputtering on the surface of the carbon nanotubes.

Benefits of technology

It achieves high specific capacity, excellent electrochemical cycling performance and excellent rate performance, alleviates the volume expansion problem of silicon, and improves the energy density and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852398A_ABST
    Figure CN119852398A_ABST
Patent Text Reader

Abstract

The invention discloses a binder-free silicon / carbon nanotube composite carbon fiber negative electrode material, a preparation method thereof and an application of the binder-free silicon / carbon nanotube composite carbon fiber negative electrode material in a lithium ion structure energy storage composite material. Carbon fibers are used as a substrate, catalyst nanowires are grown through a hydrothermal method, then dicyandiamide is used as a carbon source and a nitrogen source through a chemical vapor deposition method, and the binder-free silicon / carbon nanotube composite carbon fiber negative electrode material is prepared. Uniform and compact carbon nanotubes are uniformly grown on the surfaces of the carbon fibers, and then nano silicon is uniformly sputtered on a carbon nanotube substrate supported by the carbon fibers through a radio frequency plasma magnetron sputtering technology. A carbon nanotube material and a silicon material are effectively compounded together, the advantages of carbon and silicon are combined, and a synergistic effect is achieved. When the obtained silicon-carbon composite material is used as a negative electrode material of a lithium ion structure energy storage composite material, excellent electrochemical performance and cycling stability are shown, and the flexible structure and excellent mechanical performance ensure efficient use of the material in different fields and different application scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a flexible binderless carbon fiber composite negative electrode material of a lithium ion structure energy storage composite material, and in particular to a binderless silicon / carbon nanotube composite carbon fiber negative electrode material, a preparation method thereof and application in a lithium ion structure energy storage composite material. Background Art

[0002] The functionalization of structural materials and the structuring of functional materials are the development trends of composite materials in the future. Lightweight structural energy storage multifunctional integrated composite materials have both structural bearing and energy storage functions. They can meet the demand for materials in the development of lightweight, electrified and intelligent advanced equipment, and have broad application prospects in the fields of automobiles, robots, wind power, military industry, aerospace, etc.

[0003] Negative electrode materials are an important component of structural energy storage composite materials. Graphite materials are currently the most common negative electrode materials, with a theoretical specific capacity of 372mAh / g. The better artificial graphite in the industry has reached about 350mAh / g, and there is basically no room for improvement. However, with the rapid development of the new energy field, electric vehicles and large-scale power storage systems have become an inevitable development direction, and graphite materials have a low specific capacity and it is difficult to meet the needs of the new energy field. Therefore, one of the solutions that can effectively improve the energy density of the battery cell in terms of negative electrode materials is to develop and utilize new negative electrode materials with high specific capacity.

[0004] Silicon is the material with the highest theoretical specific capacity among the negative electrode materials discovered so far. Since each silicon atom can combine with about four lithium ions, its theoretical specific capacity is 10 times that of graphite and its operating voltage is low (its mass specific capacity can reach 4200mAh / g and its volume specific capacity can reach 9786mAh / cm 2 , but the volume change rate is also the largest. Therefore, during the battery cycle, the silicon negative electrode will inevitably expand in volume, leading to battery failure.

[0005] Compared with silicon, carbon materials have better conductivity, and the volume expansion problem during the cycle is far less obvious than that of silicon materials, which makes their electrochemical cycle stability far better than that of silicon materials. Mixing the two to form silicon-carbon materials is an effective means. The mixture of carbon and silicon forms a silicon-carbon-based composite negative electrode material, which not only combines the good conductivity of carbon and the high specific capacity of silicon, but also when the carbon material is used as the substrate, it can effectively buffer the expansion of silicon, thereby improving the overall electrochemical cycle performance of the material.

[0006] As an industrial-scale method, magnetron sputtering is widely used for the deposition of high-purity functional materials due to its simplicity, ease of operation and high efficiency. Specifically, the controllable construction of nanostructures of electrode materials on substrates based on magnetron sputtering is very promising because of the following aspects: (1) High density of sputtering; (2) Excellent adhesion between substrate and sputtered material; (3) Regardless of the melting temperature of the material, this technology can achieve low-temperature, high-deposition-rate sputtering; (4) Easy to control the ratio of sputtered composite materials; (5) The material is easily oxidized, and complex compounds are difficult to synthesize using ordinary chemical techniques, but can be achieved using magnetron sputtering technology using corresponding target materials.

[0007] Based on the above advantages, magnetron sputtering technology has been considered as an attractive auxiliary method for preparing electrode materials in recent years. The reason is that the active material is deposited on the current collector or precursor, and the sputtered material can be used directly as an electrode without the need for other added binders and conductive agents, thereby achieving higher specific capacity, excellent battery cycle performance and excellent rate performance. At the same time, the active material can be sputtered on a flexible substrate as an electrode material, which can meet the needs of current flexible wearable devices.

[0008] The present invention uses carbon nanotubes uniformly grown on carbon fiber as a base material, wherein the carbon fiber is used as a flexible base and is suitable for flexible electronic devices. The dense carbon nanotubes provide a large surface area for the deposition of silicon, prevent the agglomeration and accumulation of nano-silicon, and provide more active sites during the lithiation process. Carbon nanotubes CNT have the advantages of small diameter, large specific surface area, excellent electrical conductivity, good mechanical properties, good flexibility, etc., which can alleviate the volume expansion of silicon. The unique structural design combines the excellent electrical conductivity of carbon nanotubes with the high theoretical capacity of silicon, and they complement each other. The carefully designed carbon nanotube skeleton provides excellent protection for the stability of electrochemical cycles, and the introduction of silicon achieves a higher energy density. Summary of the invention

[0009] The purpose of the present invention is to provide a binder-free silicon / carbon nanotube composite carbon fiber negative electrode material, a preparation method thereof and its application in lithium ion structure energy storage composite materials, and to provide an effective, simple process, low cost and high efficiency technical method to prepare silicon / carbon nanotube composite lithium ion structure energy storage composite negative electrode material, effectively combining nano silicon material and carbon nanotube material, fully combining the advantages of nano silicon and carbon nanotubes, and playing a synergistic role. Flexible carbon fiber is used as a substrate, and carbon nanotubes are uniformly grown on carbon fiber by chemical vapor deposition. The dense carbon nanotubes provide a large amount of surface area for the deposition of silicon, prevent the agglomeration and accumulation of nano silicon, and provide more active sites during the lithiation process. Explore and optimize various conditions of magnetron sputtering, select the most suitable conditions for sputtering nano silicon on carbon fiber supported carbon nanotube substrates, and thus design a final material with excellent morphology, uniform silicon / carbon nanotube combination and excellent and stable electrochemical performance.

[0010] Based on the above purpose, the technical solution adopted by the present invention is: A method for preparing a binder-free silicon / carbon nanotube composite carbon fiber negative electrode material comprises taking carbon fiber as a substrate, hydrothermally growing hydroxide nanowires, then chemically vapor depositing and growing carbon nanotubes, and magnetron sputtering nanosilicon on the surface of the carbon nanotubes to obtain the negative electrode material.

[0011] Furthermore, the carbon fiber needs to be pretreated before use. The specific process is: put the cut-to-size carbon fiber into a potassium permanganate solution for ultrasonic treatment for 5 to 30 minutes, repeatedly ultrasonically clean it with deionized water and alcohol (to remove excess potassium permanganate), and then dry the cleaned carbon fiber. Drying is preferably carried out in a vacuum drying oven at 50 to 80°C for 10 to 15 hours. Preferably, the concentration of the potassium permanganate solution is 5 wt% to 15 wt%.

[0012] Further, the process of hydrothermal growth of hydroxide nanowires is as follows: Dissolve nickel nitrate, iron nitrate, ammonium fluoride and urea in deionized water in turn, stir to obtain a mixed solution, put carbon fiber into the mixed solution, perform hydrothermal reaction at 100-150°C for 1-10 h, cool to room temperature, take out the sample, wash and dry to obtain carbon fiber with hydroxide nanowires grown on the surface. Drying is preferably carried out in a vacuum drying oven at 50-80°C for 10-15 h.

[0013] Preferably, the molar ratio of nickel nitrate, ferric nitrate, ammonium fluoride and urea is (0.8-1):(0.8-1):(4-6):(9-11), specifically (0.8-1):(0.8-1):5:10, and the concentration of ferric nitrate in deionized water is 0.02-0.03 mol / L.

[0014] Further, the process of growing carbon nanotubes by chemical vapor deposition is as follows: Place the carbon fiber with hydroxide nanowires grown on the surface downstream of the quartz tube furnace, then weigh 2-3 g of dicyandiamide and put it in a corundum boat, and place it at the upstream air inlet of the quartz tube furnace. Use argon to sweep the air in the quartz tube, adjust the gas flow rate to 10-50 sccm, keep it at 350-450℃ for 1-3 h, and then keep it at 750-850℃ for 1-3 h, cool it to room temperature and take it out.

[0015] Furthermore, the process of magnetron sputtering nano-silicon on the surface of carbon nanotubes is as follows: The carbon fiber on which the carbon nanotubes are grown is fixed on the substrate of the magnetron sputtering apparatus, and the Si target is fixed on the RF target column for sputtering deposition of nano-silicon. The sputtering pressure is 0.5~5 Pa, the sputtering power is 50~150W, the sputtering time is 10-40min, and the working gas during sputtering is argon.

[0016] The binder-free silicon / carbon nanotube composite carbon fiber negative electrode material prepared by the preparation method.

[0017] Application of binder-free silicon / carbon nanotube composite carbon fiber negative electrode material as negative electrode in lithium ion structural energy storage composite materials.

[0018] This process uses dicyandiamide as the N source and C source, and hydroxide nanowires as catalyst precursors to synthesize carbon nanotubes. When calcined at high temperature in an argon inert gas atmosphere, the hydroxide nanowires formed on the surface of the carbon fiber will be reduced to metal nanoparticles, and during the annealing process, they catalyze the conversion of dicyandiamide into N-doped carbon nanotubes wrapped with metal nanoparticles. The flexible binder-free electrode material prepared by the present invention can be directly applied to the direction of lithium-ion structure energy storage composite materials, and the material is used as a negative electrode material. The silicon / carbon nanotube negative electrode material of this invention has a large number of active sites, uniform distribution of nanosilicon, and stable combination of silicon / carbon nanotubes, so it has excellent and stable electrochemical properties.

[0019] Compared with the prior art, the advantages of the present invention are: (1) The carbon fiber-supported carbon nanotube substrate is an excellent conductor of electrons, and its conductivity is better than that of semiconductor silicon. The composite with silicon improves the conductivity of the electrode to a certain extent. (2) The prepared carbon fiber-supported carbon nanotube substrate has very excellent mechanical, electrical and thermal properties, stable physical and chemical properties, and can act as a buffer matrix to inhibit and alleviate the volume change of silicon during lithium insertion and extraction, thereby enhancing the volume expansion tolerance of the silicon electrode; (3) Carbon nanotube materials have a very high specific surface area. When combined with silicon, they can not only provide lithium storage capacity, but also shorten the transmission distance of lithium ions in the electrode material and increase the lithiation reaction rate of silicon. (4) Carbon nanotubes can serve as an isolation layer between silicon and the electrolyte, preventing silicon from agglomerating and side reactions with the electrolyte. In addition, their own volume effect is small and they can form a relatively stable SEI film on the surface.

[0020] (5) Low-cost and efficient plasma magnetron sputtering technology is used to prepare electrode materials, so that nano-silicon is deposited on a carbon nanotube substrate supported by carbon fibers. The sputtered material can be used directly as an electrode without the need for other added adhesives and conductive agents, thereby achieving a higher specific capacity, excellent battery cycle performance and excellent rate performance. At the same time, the active material can be sputtered as an electrode material on a flexible substrate to meet the needs of current flexible wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a high-resolution microscopic morphology of the material under a scanning electron microscope (SEM) at a sputtering pressure of 3 Pa in the preparation of Example 1; Figure 2 This is a high-resolution microscopic morphology of the material under a scanning electron microscope (SEM) at a sputtering pressure of 2 Pa in the preparation of Example 2; Figure 3 This is a high-resolution microscopic morphology under a scanning electron microscope (SEM) at a sputtering pressure of 1 Pa in the preparation of Example 3; Figure 4 This is a high-resolution microscopic morphology of the material under a scanning electron microscope (SEM) at a sputtering pressure of 0.5 Pa in the preparation of Example 4; Figure 5 The high-resolution microscopic morphology of the material prepared in Example 5 under a scanning electron microscope (SEM); Figure 6 The high-resolution microscopic morphology of the material prepared in Example 6 under a scanning electron microscope (SEM); Figure 7 The high-resolution microscopic morphology of the material prepared in Example 7 under a scanning electron microscope (SEM); Figure 8 The high-resolution microscopic morphology of the material prepared in Example 8 under a scanning electron microscope (SEM); Fig. 9 The high-resolution microscopic morphology of the material prepared in Comparative Example 1 under a scanning electron microscope (SEM); Fig.10 Comparison of the cycling stability of the final samples of Examples 2 and 3 at 2.5C; Fig.11 Comparison of the cycling stability of the materials prepared in Examples 3 and 4 at 1C; Fig.12 Comparison of the cycle stability of Examples 5 and 6 and Comparative Examples 1 and 2 at 2.5C. DETAILED DESCRIPTION

[0022] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the embodiments described in this specification are only for explaining the present invention, not for limiting the present invention, and the parameters, proportions, etc. of the embodiments can be selected according to local conditions without substantial impact on the results.

[0023] Example 1 A method for preparing a binder-free silicon / carbon nanotube composite carbon fiber negative electrode material specifically comprises the following steps: (1) Pretreatment of carbon fiber The carbon fiber was cut into small pieces of 3 cm × 4 cm, and then added to the prepared 10 wt.% potassium permanganate solution for ultrasonic treatment for 10 min. The excess potassium permanganate was removed by repeated ultrasonic treatment with deionized water and alcohol, and then the treated clean carbon fiber was placed in a vacuum drying oven at 60 °C for 12 h.

[0024] (2) Hydrothermal growth of hydroxide nanowires Weigh 0.388 g (0.96 mmol) of Fe(NO3)3·9H2O, 0.27 g (0.93 mmol) of Ni(NO3)2·6H2O, 0.186 g (5 mmol) of NH4F, and 0.6 g (10 mmol) of urea, dissolve them in 40 mL of deionized water and stir for half an hour. Put the carbon fiber pretreated in step (1) into it, and then transfer it to a 50 mL hydrothermal reactor and keep it in an oven at 120°C for 6 h. After cooling to room temperature, take out the sample, wash the excess catalyst several times with deionized water and alcohol, and then dry it in a vacuum drying oven at 60°C for 12 h.

[0025] (3) Chemical vapor deposition growth of carbon nanotubes High-quality carbon nanotubes are grown by chemical vapor deposition (CVD). The carbon fiber with grown hydroxide nanowires obtained in step (2) is used as a template and calcined in an argon atmosphere, and dicyandiamide is used as a carbon source for growing carbon nanotubes. Specifically, the carbon fiber with grown hydroxide nanowires is placed in a high-temperature tube furnace, and it is placed downstream of the quartz tube furnace. Then 2.5g of dicyandiamide is weighed and placed in a corundum boat, which is placed at the upstream air inlet of the quartz tube furnace. The air in the quartz tube is swept with argon gas, and the gas flow rate is adjusted to 30 sccm. After being kept at 400℃ for 2 hours, the temperature is continued to rise to 800℃, and then kept at 800℃ for 2 hours, the temperature is cooled to room temperature and taken out, and finally the carbon fiber substrate for growing carbon nanotubes is obtained.

[0026] (4) Magnetron sputtering nano-silicon Magnetron sputtering nano-silicon is prepared by radio frequency (RF) magnetron sputtering. Specifically, the carbon fiber substrate for growing carbon nanotubes prepared in step (3) is first fixed on the substrate of the magnetron sputtering instrument, and then the Si target is fixed on the RF target column to sputter and deposit nano-silicon. The working gas during sputtering is argon. The vacuum background of magnetron sputtering is controlled to be 5×10 -4 Pa, the sputtering pressure is 3Pa, the sputtering power is 100W, and the sputtering time is 20min.

[0027] The morphology of the material obtained in Example 1 was analyzed by scanning electron microscopy (SEM). Figure 1As shown, after the carbon nanotubes are uniformly grown on the carbon fibers, no deposition of nano-silicon is found on the surface of the carbon nanotubes under a sputtering pressure of 3Pa by magnetron sputtering, and the morphology of the carbon nanotubes is the same as that on the initial carbon fibers. It can be concluded that nano-silicon cannot be sputtered under a sputtering pressure of 3Pa.

[0028] Example 2 A method for preparing a binder-free silicon / carbon nanotube composite carbon fiber negative electrode material specifically comprises the following steps: (1) This step is the same as step (1) in Example 1.

[0029] (2) This step is the same as step (2) in Example 1.

[0030] (3) This step is the same as step (3) in Example 1.

[0031] (4) First, fix the carbon fiber substrate for growing carbon nanotubes prepared in step (3) on the substrate of the magnetron sputtering instrument, and then fix the Si target on the RF target column to sputter and deposit nano-silicon. The working gas during sputtering is argon. The vacuum background of the magnetron sputtering is controlled to be 5×10 -4 Pa, the sputtering pressure is 2Pa, the sputtering power is 100W, and the sputtering time is 20min.

[0032] The morphology of the material obtained in Example 2 was analyzed by scanning electron microscopy (SEM). Figure 2 As shown in the figure, after the carbon nanotubes are grown on the carbon fiber, some of the carbon nanotubes are obviously surrounded by nano-silicon and their diameters become thicker, but some carbon nanotubes are not deposited with nano-silicon, showing unevenness. It can be concluded that the sputtering is not sufficient under the sputtering pressure of 2 Pa. Many carbon nanotubes are not sputtered, while some are sputtered too much and do not have good uniformity.

[0033] Example 3 A method for preparing a binder-free silicon / carbon nanotube composite carbon fiber negative electrode material specifically comprises the following steps: (1) This step is the same as step (1) in Example 1.

[0034] (2) This step is the same as step (2) in Example 1.

[0035] (3) This step is the same as step (3) in Example 1.

[0036] (4) First, fix the carbon fiber substrate for growing carbon nanotubes prepared in step (3) on the substrate of the magnetron sputtering instrument, and then fix the Si target on the RF target column to sputter and deposit nano-silicon. The working gas during sputtering is argon. The vacuum background of the magnetron sputtering is controlled to be 5×10-4 Pa, the sputtering pressure is 1Pa, the sputtering power is 100W, and the sputtering time is 20min.

[0037] The morphology of the material obtained in Example 3 was analyzed by scanning electron microscopy (SEM). Figure 3 As shown, after the carbon nanotubes are grown on the carbon fibers, under a sputtering pressure of 1 Pa, the deposition of nano-silicon is very uniform, the surface of the carbon nanotubes is obviously evenly covered with nano-silicon, each carbon nanotube is uniform in thickness, and there is no agglomeration or accumulation of nano-silicon, which lays the foundation for excellent electrochemical performance.

[0038] Example 4 A method for preparing a binder-free silicon / carbon nanotube composite carbon fiber negative electrode material specifically comprises the following steps: (1) This step is the same as step (1) in Example 1.

[0039] (2) This step is the same as step (2) in Example 1.

[0040] (3) This step is the same as step (3) in Example 1.

[0041] (4) First, fix the carbon fiber substrate for growing carbon nanotubes prepared in step (3) on the substrate of the magnetron sputtering instrument, and then fix the Si target on the RF target column to sputter and deposit nano-silicon. The working gas during sputtering is argon. The vacuum background of the magnetron sputtering is controlled to be 5×10 -4 Pa, the sputtering pressure is 0.5 Pa, the sputtering power is 100 W, and the sputtering time is 20 min.

[0042] The morphology of the material obtained in Example 4 was analyzed by scanning electron microscopy (SEM). Figure 4 As shown in the figure, after growing carbon nanotubes on carbon fiber, under the sputtering pressure of 0.5Pa, the surface of each carbon nanotube is covered with nano-silicon, but the nano-silicon undergoes agglomeration. Many nano-silicon are not deposited on the carbon nanotube skeleton, but accumulate and agglomerate on the surface. In the subsequent electrochemical reaction, the nano-silicon is prone to agglomeration and detachment, affecting the electrochemical stability.

[0043] Example 5 A method for preparing a binder-free silicon / carbon nanotube composite carbon fiber negative electrode material specifically comprises the following steps: (1) This step is the same as step (1) in Example 1.

[0044] (2) This step is the same as step (2) in Example 1.

[0045] (3) This step is the same as step (3) in Example 1.

[0046] (4) First, fix the carbon fiber substrate for growing carbon nanotubes prepared in step (3) on the substrate of the magnetron sputtering instrument, and then fix the Si target on the RF target column to sputter and deposit nano-silicon. The working gas during sputtering is argon. The vacuum background of the magnetron sputtering is controlled to be 5×10 -4 Pa, the sputtering pressure is 1Pa, the sputtering power is 100W, and the sputtering time is 10min.

[0047] The morphology of the material obtained in Example 5 was analyzed by scanning electron microscopy (SEM). Figure 5 As shown, after the carbon nanotubes are grown on the carbon fibers, under a sputtering pressure of 1 Pa, a small amount of nano-silicon is deposited on the surface of the carbon nanotubes after a sputtering time of 10 min. The sputtering is uniform, and the diameter of the silicon carbon nanotubes after sputtering for 10 min increases less, indicating that the loading of nano-silicon is less.

[0048] Example 6 A method for preparing a binder-free silicon / carbon nanotube composite carbon fiber negative electrode material specifically comprises the following steps: (1) This step is the same as step (1) in Example 1.

[0049] (2) This step is the same as step (2) in Example 1.

[0050] (3) This step is the same as step (3) in Example 1.

[0051] (4) First, the carbon fiber substrate for growing carbon nanotubes prepared in step (3) is fixed on the substrate of the magnetron sputtering instrument, and then the Si target is fixed on the RF target column to perform sputtering deposition of nano-silicon. The working gas during sputtering is argon. The vacuum background of the magnetron sputtering is controlled to be 5×10 -4 Pa, the sputtering pressure is 1Pa, the sputtering power is 100W, and the sputtering time is 20min.

[0052] The morphology of the material obtained in Example 6 was analyzed by scanning electron microscopy (SEM). Figure 6 As shown, after growing carbon nanotubes on carbon fibers, under a sputtering pressure of 1 Pa and a sputtering time of 20 min, nanosilicon is deposited evenly on the carbon nanotubes, the diameter of the carbon nanotubes is further expanded, and the deposition of nanosilicon on the surface becomes more obvious.

[0053] Example 7 A method for preparing a binder-free silicon / carbon nanotube composite carbon fiber negative electrode material specifically comprises the following steps: (1) This step is the same as step (1) in Example 1.

[0054] (2) This step is the same as step (2) in Example 1.

[0055] (3) This step is the same as step (3) in Example 1.

[0056] (4) First, fix the carbon fiber substrate for growing carbon nanotubes prepared in step (3) on the substrate of the magnetron sputtering instrument, and then fix the Si target on the RF target column to sputter and deposit nano-silicon. The working gas during sputtering is argon. The vacuum background of the magnetron sputtering is controlled to be 5×10 -4 Pa, the sputtering pressure is 1Pa, the sputtering power is 100W, and the sputtering time is 30min.

[0057] The morphology of the material obtained in Example 7 was analyzed by scanning electron microscopy (SEM). Figure 7 As shown, after the carbon nanotubes are grown on the carbon fibers, at a sputtering pressure of 1 Pa and a sputtering time of 30 min, the nano-silicon is deposited evenly on the carbon nanotubes, the diameter of the carbon nanotubes is further expanded, and the deposition of nano-silicon on the surface is further increased.

[0058] Example 8 A method for preparing a binder-free silicon / carbon nanotube composite carbon fiber negative electrode material specifically comprises the following steps: (1) This step is the same as step (1) in Example 1.

[0059] (2) This step is the same as step (2) in Example 1.

[0060] (3) This step is the same as step (3) in Example 1.

[0061] (4) First, fix the carbon fiber substrate for growing carbon nanotubes prepared in step (3) on the substrate of the magnetron sputtering instrument, and then fix the Si target on the RF target column to sputter and deposit nano-silicon. The working gas during sputtering is argon. The vacuum background of the magnetron sputtering is controlled to be 5×10 -4 Pa, the sputtering pressure is 1Pa, the sputtering power is 100W, and the sputtering time is 40min.

[0062] The morphology of the material obtained in Example 8 was analyzed by scanning electron microscopy (SEM). Figure 8 As shown, after growing carbon nanotubes on carbon fiber, under a sputtering pressure of 1Pa, the sputtering time is 40min, the diameter of the carbon nanotubes is significantly enlarged, and after silicon is deposited, it is very full and three-dimensional, and no agglomeration of nano-silicon is found, indicating that the sputtering is uniform.

[0063] Comparative Example 1: (1) Pretreatment of carbon fiber The carbon fiber was cut into small pieces of 3 cm × 4 cm, and then added to the prepared 10 wt.% potassium permanganate solution for ultrasonic treatment for 10 min. The excess potassium permanganate was removed by repeated ultrasonic treatment with deionized water and alcohol, and then the treated clean carbon fiber was placed in a vacuum drying oven at 60 °C for 12 h.

[0064] (2) Hydrothermal growth of hydroxide nanowires Weigh 0.388 g of Fe(NO3)3·9H2O, 0.27 g of Ni(NO3)2·6H2O, 0.186 g of NH4F, and 0.6 g of urea, dissolve them in 40 mL of deionized water and stir for half an hour. Put the carbon fiber pretreated in step (1) into the solution, and then transfer it to a 50 mL hydrothermal reactor and keep it in an oven at 120°C for 6 h. After cooling to room temperature, take out the sample, wash the excess catalyst several times with deionized water and alcohol, and then dry it in a vacuum drying oven at 60°C for 12 h.

[0065] (3) Chemical vapor deposition growth of carbon nanotubes High-quality carbon nanotubes are grown by chemical vapor deposition (CVD). The carbon fiber with grown hydroxide nanowires obtained in step (2) is used as a template and calcined in an argon atmosphere, and dicyandiamide is used as a carbon source for growing carbon nanotubes. Specifically, the carbon fiber with grown hydroxide nanowires is placed in a high-temperature tube furnace, and it is placed downstream of the quartz tube furnace. Then 2.5g of dicyandiamide is weighed and placed in a corundum boat, which is placed at the upstream air inlet of the quartz tube furnace. The air in the quartz tube is swept with argon, and the gas flow rate is adjusted to 30 sccm. After being kept at 400°C for 2 hours, the temperature is continuously raised to 800°C and kept at 800°C for another 2 hours, and then the temperature is cooled to room temperature and taken out, and finally the carbon fiber substrate with grown carbon nanotubes is obtained.

[0066] By growing carbon nanotubes only on carbon fibers without sputtering silicon as a comparative sample, the morphology of the material obtained in Comparative Example 1 was analyzed by scanning electron microscopy (SEM). Fig. 9 As shown, only uniform carbon nanotubes were grown on the carbon fibers without silicon being deposited by magnetron sputtering.

[0067] Comparative Example 2: (1) This step is the same as step (1) in Comparative Example 1.

[0068] By simply treating the carbon fibers to increase their hydrophilicity, no other steps were performed to evaluate the capacity contribution of pure carbon fibers in the electrode.

[0069] Application Examples The negative electrode materials of Examples 2 to 6 and Comparative Examples 1 and 2 were cut into 1.2 cm diameter discs and directly used as working electrodes without other binders, current collectors and conductive agents. Lithium metal was used as the counter electrode and assembled into button batteries. The button battery structure from bottom to top is: positive electrode shell, material, electrolyte (LX-031, formula is 1M LiPF6in DEC:DMC:EC=1:1:1 Vol% with 5%FEC), diaphragm (Celgard 2500), electrolyte (same as above), lithium sheet, gasket, spring positive electrode shell, the same electrolyte was added on both sides of the diaphragm, and the cycle performance was tested on the Blue Electric test platform. The results are detailed in Figures 10 to 12 .

[0070] First, the assembled button cell was activated at 0.5 C for 4 cycles, and then cycled at 2.5 C for 100 cycles. Fig.10 As shown in the figure, it can be seen that the initial discharge capacity of the material in Example 3 (i.e., the sputtering pressure is 1 Pa) at 2.5 C is about 1850 mAh g -1 The specific capacity of the 5th cycle at 2.5 C is about 1250 mAh g -1 After 100 cycles, the specific capacity is about 1050 mAh g -1 The capacity retention rate is about 84%. It shows excellent stability. The initial discharge capacity of the material in Example 2 (i.e., the sputtering pressure is 2 Pa) at 2.5 C is about 1300 mAh g -1 The specific capacity at 2.5 C in the 5th cycle is about 750 mAh g -1 After 100 cycles, the specific capacity is about 480 mAh g -1 , the capacity retention rate is 64%. Therefore, by comparison, the material of Example 3 is obviously superior to the material of Example 2 in terms of specific capacity and cycle stability.

[0071] Fig.11 It can be seen that the initial discharge capacity of the material in Example 3 (i.e., the sputtering pressure is 1 Pa) at 1C is about 2150 mAh g -1 , the specific capacity at 1 C in the 5th cycle is about 1450 mAh g -1 After 70 cycles, the specific capacity is about 1400 mAh g -1 The capacity retention rate is 96.5%. It shows excellent stability. The initial discharge capacity of the material in Example 4 (i.e., the sputtering pressure is 0.5 Pa) at 1 C is about 1980 mAh g -1 , the specific capacity at 1 C in the 5th cycle is about 1300 mAh g -1 After 70 cycles, the specific capacity is about 1250 mAh g -1, the capacity retention rate is 96.1%. Therefore, by comparison, the material of Example 3 is obviously superior to the material of Example 4 in terms of specific capacity and cycle stability.

[0072] Fig.12 The initial discharge capacity of the material in Example 6 at 2.5C is about 1850 mAh g -1 , the 5th cycle 2.5 C is about 1250 mAh g -1 After 100 cycles, the specific capacity is about 1050 mAh g -1 The capacity retention rate is 84%. The initial discharge capacity of the material in Example 5 at 2.5C is about 1300 mAh g -1 The specific capacity at 2.5 C in the 5th cycle is about 750 mAh g -1 After 100 cycles, the specific capacity is about 550 mAh g -1 The capacity retention rate is 73.3%. The initial discharge capacity of the material in comparative example 1 at 2.5C is about 900mAh g -1 The specific capacity of the 5th cycle at 2.5 C is about 350 mAh g -1 After 100 cycles, the specific capacity is about 250 mAh g -1 The capacity retention rate is 71.4%. The first discharge capacity of the material in comparative example 2 at 2.5 C is about 100 mAh g -1 The specific capacity of the 5th cycle at 2.5 C is about 35 mAh g -1 After 100 cycles, the specific capacity is about 30 mAh g -1 , the capacity retention rate is 85.7%, and the specific capacity is very low. Therefore, by comparison, the material of Example 6 shows obvious advantages in specific capacity and cycle stability.

Claims

1. A method for preparing a binder-free silicon / carbon nanotube composite carbon fiber negative electrode material, characterized in that: The method comprises the following steps: taking carbon fiber as substrate, hydrothermally growing hydroxide nanowires, then chemically vapor depositing and growing carbon nanotubes, and magnetron sputtering nano-silicon on the surface of the carbon nanotubes to obtain the product.

2. The preparation method according to claim 1, characterized in that The carbon fiber needs to be pretreated before use. The specific process is: the cut-to-size carbon fiber is placed in a potassium permanganate solution for ultrasonic treatment for 5 to 30 minutes, and is repeatedly ultrasonically cleaned with deionized water and alcohol, and then the cleaned carbon fiber is dried.

3. The preparation method according to claim 1, characterized in that: The process of hydrothermal growth of hydroxide nanowires is as follows: Dissolve nickel nitrate, iron nitrate, ammonium fluoride and urea in deionized water in turn, stir to obtain a mixed solution, and put carbon fiber into the mixed solution. The hydrothermal reaction is carried out at 100-150° C. for 1 h-10 h, and after cooling to room temperature, the sample is taken out, washed, and dried to obtain carbon fibers with hydroxide nanowires grown on the surface.

4. The preparation method according to claim 3, characterized in that: The molar ratio of nickel nitrate, ferric nitrate, ammonium fluoride and urea is (0.8~1):(0.8~1):(4~6):(9~11), and the concentration of ferric nitrate in deionized water is 0.02~0.03 mol / L.

5. The preparation method according to claim 1, characterized in that: The process of growing carbon nanotubes by chemical vapor deposition is as follows: Place the carbon fiber with hydroxide nanowires grown on the surface downstream of the quartz tube furnace, then weigh 2-3 g of dicyandiamide and put it in a corundum boat, and place it at the upstream air inlet of the quartz tube furnace. Use argon to sweep the air in the quartz tube, adjust the gas flow rate to 10-50 sccm, keep it at 350-450℃ for 1-3 h, and then keep it at 750-850℃ for 1-3 h, cool it to room temperature and take it out.

6. The preparation method according to claim 1, characterized in that: The process of magnetron sputtering nano-silicon on the surface of carbon nanotubes is as follows: the carbon fiber on which the carbon nanotubes are grown is fixed on the substrate of the magnetron sputtering instrument, the Si target is fixed on the RF target column, and nano-silicon is sputtered and deposited. The sputtering pressure is 0.5~5 Pa, the sputtering power is 50~150W, the sputtering time is 10~40min, and the working gas during sputtering is argon.

7. The binder-free silicon / carbon nanotube composite carbon fiber negative electrode material prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the binder-free silicon / carbon nanotube composite carbon fiber negative electrode material according to claim 7 as a negative electrode in a lithium ion structure energy storage composite material.

Citation Information

Patent Citations

  • Silicon-based composite negative electrode plate, preparation method, and lithium ion secondary battery

    CN107799723A

  • Lithium metal battery three-dimensional double-layer structure negative electrode material and preparation method thereof

    CN113809300A

  • Preparation method of nickel-cobalt selenide supported platinum catalyst

    CN116314871A

  • Preparation method and application of bifunctional catalyst for hydrogen evolution and oxygen evolution reaction

    CN116641091A

  • Hybrid nanostructured materials and methods

    US20160301066A1

Cited By

  • Carbon material of road network structure, preparation method and application in supercapacitor

    CN120545101A